2008
DOI: 10.1002/ejoc.200800872
|View full text |Cite
|
Sign up to set email alerts
|

Prins Cyclization in Ionic Liquid Hydrogen Fluoride Salts: Facile and Highly Efficient Synthesis of 4‐Fluorinated Tetrahydropyrans, Thiacyclohexanes, and Piperidines

Abstract: Prins cyclization of homoallylic alcohols with various aldehydes was investigated in ionic liquid hydrogen fluoride (HF) salts, which played roles as a reaction medium, a catalyst, and a fluorine source. The reaction afforded the corresponding 4‐fluorinated tetrahydropyrans in excellent yields with a high stereoselectivity (cis form exclusively). When benzaldehydes having a strongly electron‐donating group at the para position were used, the stereoselectivity was lost in this system. In order to apply this met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 49 publications
0
62
1
Order By: Relevance
“…Many Lewis acids have been used in the Prins reaction, most commonly giving a halogen at the 4-position of the tetrahydropyran: in our own work and from others Cl from InCl 3 or Br from InBr 3 ; 10,11 other examples (but not a complete listing) include fluorine from BF 3 $OEt 2 , 12e14 HBF 4 15 or Et 4 NF/5HF; 16 25 TMSCl/NaI, 26 TiI 4 /I 2 7 or I 2 . 27 More interestingly, there are a few examples of oxygenated nucleophiles incorporated, including OAc from BF 3 $OEt 2 /AcOH/TMSOAc; 28 OH indirectly from TFA.…”
Section: Lewis Acids In the Prins Reactionmentioning
confidence: 97%
“…Many Lewis acids have been used in the Prins reaction, most commonly giving a halogen at the 4-position of the tetrahydropyran: in our own work and from others Cl from InCl 3 or Br from InBr 3 ; 10,11 other examples (but not a complete listing) include fluorine from BF 3 $OEt 2 , 12e14 HBF 4 15 or Et 4 NF/5HF; 16 25 TMSCl/NaI, 26 TiI 4 /I 2 7 or I 2 . 27 More interestingly, there are a few examples of oxygenated nucleophiles incorporated, including OAc from BF 3 $OEt 2 /AcOH/TMSOAc; 28 OH indirectly from TFA.…”
Section: Lewis Acids In the Prins Reactionmentioning
confidence: 97%
“…For this study, enantiopure alcohols were reacted with aldehydes to access fluorinated tetrahydropyrans In 2008, Fuchigami and coworkers developed a Prins fluorocyclization in ionic liquids [25,26]. Since previous work had demonstrated that ionic liquid HF salts such as Et 3 N3HF are suitable for fluorinations, the authors envisaged that such HF salts could act as a protic acid catalyst for Prins fluorocyclizations.…”
Section: Mini-review | Wilkinson Salmon and Gouverneurmentioning
confidence: 97%
“…When 4methylene6 phenylhexanoic acid was treated in acetonitrile with 25 and NaHCO 3 , the desired product 26 was obtained in only 12% yield. The protocy clized product 27 was isolated in 44% yield along with 7% yield of the fluorinated lactam 28, a product resulting from the participation of the [28].…”
Section: Fluorocyclizations Featuring An Electrophilic Fluorinationmentioning
confidence: 98%
“…This remarkable cascade assembles the macrocycle, introduces a fluorine atom at the C13 position, and achieves global removal all the silyl protecting groups to give the fluoro derivative 13 (Scheme 4). This transformation is only the second example of a hydrogen fluoride promoted Prins reaction, 34 and only the second report of a fluoro-Prins macrocyclization. 28 Although not yet optimized in terms reaction time, the reaction provides a one-step route to fluorine-labeled analogues.…”
mentioning
confidence: 95%